ANALISIS PREFERENSI KONSUMEN TERHADAP ATRIBUT BUAH PISANG DI KOTA MATARAM - Sastrawan, Nilul Irfana; Budastra, I Ketut; Efendy, Efendy (JURNAL AGRIMANSION, 2023)
This study aims to analyze consumer preferences for banana attributes in Mataram City using a descriptive method, as many as 100 respondents in Mataram City selected using a systematic random sampling method. Determination of the sample area is carried out by purposive sampling. Data collection with survey techniques, namely interviews and questionnaire distribution. The collected data was analyzed using conjoint analysis. The results showed that the attributes of bananas most considered by consumers based on importance value in order were freshness, ripening, price, type of banana, and safety label. The attributes of bananas that become consumer preferences based on the value of usefulness are the type of yellow banana, fresh conditions, natural ripening, there is a safety label, and prices range from Rp. 12,000-18,000/kg.